تحسين الخواص الميكانيكية للبولي استر غير المشبع المدعم بألياف زجاجية عشوائية المستخدم في تصنيع شفرة عنفة ريحية - كفا, سمير; النجار, رائد; صوفي, ليال (Latakia University Journal -Engineering Sciences Series, 2017)
نتيجة لتطور مجال استخدام المركّبات المدعمة بالألياف في التطبيقات العملية بشكل مستمر يهدف البحث الى دراسة تأثير نسبة المواد البيروكسيدية المضافة الى مادة البولي استر غير المشبع على خواص الشد لعينات محضرة من البولي الاستر غير المشبع المدعم بالألياف الزجاجية المستخدمة في تصنيع شفرات توربينات الرياح، وكذلك دراسة تأثير مدة تطبيق عمليات المعالجة الحرارية على تصلب البولي استر غير المشبع وخواص عملية الشد بعد تطبيق المعالجة الحرارية بهدف تحسين خواص هذه الشفرات. تم تحضير عينات اختبار تحتوي على نسب (1% - 1.5% - 2%) من المادة البيروكسيدية ميتيل ايتيل كيتون بيروكسيد MEKP وأظهرت نتائج الاختبار أن أفضل نسبة عند 1.5%. في حين أظهرت نتائج المعالجة الحرارية أن أفضل قيم لمقاومة الشد عند الانقطاع هي للعينات المعالجة لزمن قدره /48 hours/.As a result of the development of the use of reinforced Composites with fibers in practical applications continuously, research aims to study the effect of proportion piroxide additives to unsaturated polyester resin on the tensile properties of the samples prepared from unsaturated polyester resin reinforced with glass fiber used in wind turbine blades manufacturing, and also studying the effect of for the application of heat treatment operations on the hardening of the unsaturated polyester and tensile properties after heat treatment process the application in order to improve the properties of these blades.Test samples were prepared containing ratios (1% - 1.5% - 2%) of methyl Etel ketone piroxide MEKP and test results showed that the best ratio at 1.5%. While the heat treatment results showed that the best values for tensile strength at break of the samples are treated to a time of / 48 hours /.